Overlooking the Oppression of Uyghur Muslims: Unfavorable Domestic Politics and the 'Deactivation' of Indonesia’s Islamic Diplomacy - Hasram, Khaidir (Islamic Studies Review, 2024)
This article seeks to examine whether Islam remains relevant in determining diplomatic initiatives in the current geopolitical environment. Thus, it presumes that Muslim states have Islamic tendencies in their foreign policy, but seeks to understand when and under what conditions such Islamic diplomacy is activated. In order to explore these questions, I will examine the case of the oppressed of Uyghur Muslims. Despite widespread coverage highlighting serious human rights violations targeting Uyghur Muslims, Muslim states have taken nuanced, cautious stances and in some cases remained silent. This is a slightly unexpected stance with regards to such a high-profile case of oppression of Muslims. Academic literature overemphasizes strong state partnerships, economic dependencies, and China’s significant role in international affairs as factors constraining Muslim states in activating Islamic diplomacy with regards to Uyghur Muslims. Utilizing the ‘two-level games’ framework and focusing on a single-country case study – Indonesia under Joko Widodo – this article argues that a combination of the geopolitical environment and unfavorable domestic politics have resulted in the deactivation of Islamic diplomacy on the Uyghur issue. The increasing consolidation of power during the second term of Widodo’s administration led to the decline of political Islam, referring to the declining role of formal and informal Islamic actors in domestic politics, which in turn, weakened Islamic groups’ demands for the activation of Islamic diplomacy on the Uyghur issue.